Atitude do consumidor para com o shopping center como local de compra: um estudo no Shopping Leste - Av. Aricanduva - Maya, Paulo Cesar da Cunha (1994)
The thesis measures consumer's attitude towards the Shopping Center and retailing, in function of attributes, by demographic variables for segmentation purposes. lt investigates yet other related questions, as for example media habits and credit cards use. lt is a qualitativa and quantitativa research, with hypothesis tests, in the field of study of CONSUMER BEHAVIOR under the Marketing approach, wich starts by a literatura review at world wide levei and finishes through a survey in the Shopping Center Leste - Av. Aricanduva, a regional shopping center in São Paulo city, the most important consumar center within Latin America, and one of the three biggest cities of the world in number of inhabitants. The conclusion, among other fidings, some surprising, reveals the importance of demographic variables in the measurement of consumer's attitudes towards the shopping centers and retailing, a contribution to improve Marketing strategies and tactics with the aim of better satisfy consumer's needs. The research finds toa that consumer's attitude towards the local of purchase, in function of its attributes is not different by the primary zone and others in the trade area. Offers. finally, suggestions for future research.